To solve the equation \( 5(x - 6) + 2 = 7x - 8 \), follow these steps:
-
Distribute the \( 5 \) on the left side: \[ 5x - 30 + 2 = 7x - 8 \]
-
Combine like terms on the left side: \[ 5x - 28 = 7x - 8 \]
-
Get all terms involving \( x \) on one side and constant terms on the other side. Subtract \( 5x \) from both sides: \[ -28 = 7x - 5x - 8 \] \[ -28 = 2x - 8 \]
-
Add \( 8 \) to both sides: \[ -28 + 8 = 2x \] \[ -20 = 2x \]
-
Divide both sides by \( 2 \): \[ x = -10 \]
So, the solution is \( x = -10 \).